Car Taxes and CO2 emissions in EU - Jordal-Jørgensen, Jørgen (Proceedings from the Annual Transport Conference at Aalborg University, 2001)
The fuel efficiency of passenger cars is often emphasised as one of the most significant areas of action in terms of limiting the transport sector’s CO2 emission levels. This could be achieved either on the supply side through the technological development of cars, or through demand-side measures such as influencing first time buyers’ choice of car. The aim of this article is to present a model for analysis of the demand side, more specifically the relation between the CO2 emissions from new cars and the car taxation related to new car purchases in EU. The purpose of the model is twofold. Firstly, it should be used to analyse the CO2 efficiency of the car taxation in each member state. Secondly, results from model calculations should be used to illustrate what are the possibilities for the individual member states to reduce their CO2 emissions from new cars. It should be noted that this paper mainly covers methodological aspects and results, since no CO2 reduction results are available at this stage. The model is based on a revised and enhanced version of the Danish Car Choice model from 1997 combined with car characteristics, socio-economic data and car taxation data from the EU member states.